Building Success in Online Educational Programs for Adult Learners - Matthew A. Eichler; Tani K. Bialek; Cynthia L. Digby; Cathy Twohig; Rod P. Githens; Lynn A. Trinko (Adult Education Research Conference, 2009)
The purpose of this symposium is to explore multiple perspectives on building and maintaining high quality online educational programs in university settings for adult learners.